The Rules of Rescue Cost, Distance, and Effective Altruism - Pummer, Theron (Oxford University Press, 2023)
This is a book about duties to help others. When does one have to sacrifice life and limb, time and money, to prevent harm to others? When must one save more people rather than fewer? These questions arise in emergencies involving nearby strangers who are drowning or trapped in burning buildings. But they also arise in everyday life, in which one has constant opportunities to give time or money to help distant strangers in need of food, shelter, or medical care. With the resources available, one can provide more help or less. This book argues that it is often wrong to provide less help rather than more, even when the personal sacrifice involved makes it permissible not to help at all. It shows that helping distant strangers by donating or volunteering is morally more like rescuing nearby strangers than most of us realize. The ubiquity of opportunities to help others threatens to make morality extremely demanding, and the book argues that it is only thanks to adequate permissions grounded in considerations of cost and autonomy that one may pursue one's own plans and projects. It concludes that many are required to provide no less help over their lives than they would have done if they were effective altruists.